Implementacja zabezpieczeń jako element zarządzania bezpieczeństwem systemu informacyjnego w przedsiębiorstwie - Rot, Artur; Chomiak-Orsa, Iwona (Implementation of Protections as An Element of Information System Security Management in the Enterprise, 2007)
In the contemporary Information Systems protections itself are no more sufficient as a standalone solution. Because contemporary Information Systems are very often sophisticated, heterogeneous and have dynamic character, individual solutions cannot ensure full protection against all possible threats. That is why it is worth to impose the layers of appropriate solutions which protect against its greatest number. In connection to the above very significant element of Information System security management it is appropriate the implementation of protection system and what is more the appropriate elaboration and implementation of education and awareness program. The aim of this article is introduction to the problems of IS security management and presentation of the crucial requirements concerning implementation of appropriate protections on the basis of Polish enterprises' experiences.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Informatyka Ekonomiczna (11); 2007; nr 1156, s. 58-67